The Existence of Woodball Athlete Guidance in the Indonesian Woodball Association (IWbA) of Buleleng Regency - Iragraha, S. M. Fernanda; Dewi , Putu Citra Permana; Susanto , Nugroho; Payer, Hemant; Sultoni, Kuston (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This research uses a survey method through an evaluative descriptive approach, which aims to determine the existence of woodball athlete coaching in IWbA Buleleng Regency. This research can be used as a reference for other regions to foster to produce potential woodball athletes for their regions and in the future for Indonesia. The results of this study indicate that the existence of coaching woodball athletes in IWbA Buleleng Regency is going very well, because it is supported by (1) the complete and obedient administrative profile of the Buleleng Regency IWbA organization; (2) support from agencies/institutions (Government/Disdikpora/KONI Buleleng Regency) synergistically running optimally; (3) human resources (HR) are very adequate; (4) training facilities and equipment are very complete; and (5) continuous athlete coaching is carried out. The younger generation in Buleleng Regency deserves to choose woodball sports to be involved in because (1) woodball sports are easy to learn and safe for various ages; (2) woodball sports can be pursued by men or women; (3) the price of equipment is affordable; (4) woodball sports can be used as a tool to add positive activities; (5) woodball sports can be used as a tool to build beautiful relationships; (6) woodball sports can be used as a tool to make it easier to find schools/colleges (for those who excel); (7) can make it easier to get to know the region/world through the events that are followed; and (8) woodball sports can be used as a tool to pursue an achievement sport that can be aligned with other achievement/popular sports. The obstacles faced include: (1) training programs/schedules often clash with student/athlete school schedules; (2) training programs/schedules often clash with student/athlete college schedules; (3) lack of coaching funds to participate in national/international level events; (4) students who become athletes sometimes take too long dispensation (school/college permission) when participating in championships (so that athletes become a burden on the mind because they do not participate in school/college activities); (5) the lack of attention from schools to open extra-curricular woodball sports; and (6) the Sukasada Solid Works field is still used by the surrounding community to play soccer, so that sometimes the attached fairway rope is often detached.